Effectiveness of educational outreach in infectious diseases management: a cluster randomized trial in Uganda. (December 2016) - Mbonye, Martin; Burnett, Sarah; Naikoba, Sarah; Ronald, Allan; Colebunders, Robert; Van Geertruyden, Jean-Pierre; Weaver, Marcia
Abstract Background Integrated Infectious Diseases Capacity Building Evaluation (IDCAP) teams designed and implemented two health worker in-service training approaches: 1) an off-site classroom-based integrated management of infectious diseases (IMID) course with distance learning aspects, and 2) on-site support (OSS), an educational outreach intervention. We tested the effects of OSS on workload and 12 facility performance indicators for emergency triage assessment and treatment, HIV testing, and malaria and pneumonia case management among outpatients by two subgroups: 1) mid-level practitioners (MLP) who attended IMID training (IMID-MLP) and 2) health workers who did not (No-IMID). Methods Thirty-six health facilities participated in the IDCAP trial, with 18 randomly assigned to Arm A and 18 to Arm B. Two MLP in both arms received IMID. All providers at Arm A facilities received nine monthly OSS visits from April to December 2010 while Arm B did not. From November 2009 to December 2010, 777, 667 outpatient visits occurred. We analyzed 669, 580 (86.1 %) outpatient visits, where provider cadre was reported. Treatment was provided by 64 IMID-MLP and 1, 515 No-IMID providers. The effect of OSS was measured by the difference in pre/post changes across arms after controlling for covariates (adjusted ratio of relative risks = a RRR). Results The effect of OSS on patients-per-provider-per-day (workload) among IMID-MLP (aRRR = 1.21;p = 0.48) and No-IMID (aRRR = 0.90;p = 0.44) was not statistically significant. Among IMID-MLP, OSS was effective for three indicators: malaria cases receiving an appropriate antimalarial (aRRR = 1.26, 99 % CI = 1.02-1.56), patients with negative malaria test result prescribed an antimalarial (aRRR = 0.49, 99 % CI = 0.26-0.92), and patients with acid-fast bacilli smear negative result receiving empiric treatment for acute respiratory infection (aRRR = 2.04, 99 % CI = 1.06-3.94). Among No-IMID, OSS was effective for two indicators: emergency and priority patients admitted, detained or referred (aRRR = 2.12, 99 % CI = 1.05-4.28) and emergency patients receiving at least one appropriate treatment (aRRR = 1.98, 99 % CI = 1.21-3.24). Conclusion Effects of OSS on workload were not statistically significant. Significant OSS effects on facility performance across subgroups were heterogeneous. OSS supported MLP who diagnosed and treated patients to apply IMID knowledge. For other providers, OSS supported team work to manage emergency patients. This evidence on OSS effectiveness could inform interventions to improve health workers' capacity to deliver better quality infectious diseases care.